Pre-programmed self-assembly of polynuclear clusters - Shiga, Takuya; Newton, Graham N.; Oshio, Hiroki (Royal Society of Chemistry, 2018)
This perspective reviews our recent efforts towards the self-assembly of polynuclear clusters with ditopic and tritopic multidentate ligands HL1 (2-phenyl-4,5-bis{6-(3,5-dimethylpyrazol-1-yl)pyrid-2-yl}-1H-imidazole) and H2L2 (2,6-bis-[5-(2-pyridinyl)-1H-pyrazole-3-yl]pyridine), both of which are planar and rigid molecules. HL1 was found to be an excellent support for tetranuclear [Fe4] complexes, [FeII4(L1)4](BF4)4 ([FeII4]) and [FeIII2FeII2(L1)4](BF4)6 ([FeIII2FeII2]). The homovalent system was found to exhibit multistep spin crossover (SCO), while the mixed-valence [FeIII2FeII2] complex shows wavelength-dependent tuneable light-induced excited spin state trapping (LIESST). For H2L2, a variety of polynuclear complexes were obtained through complexation with different transition metal ions, allowing the isolation of rings, grids, and helix structures. The rigidity of the ligand, difference in its coordination sites, and affinity for different metal ions dictates its coordination behaviour. In this paper, we summarise these ligand pre-programmed self-assembled clusters and their diverse physical properties.